Patients' experience of and participation in a stroke self-management programme, My Life After Stroke (MLAS): a multimethod study. Issue 11 (15th November 2022) - Blatchford, Emily Grace; Aquino, Maria Raisa Jessica; Grant, Julie; Johnson, Vicki; Mullis, Ricky; Lim, Lisa; Mant, Jonathan
Abstract : Objective: A self-management programme, My Life After Stroke (MLAS), was developed to support stroke survivors. This evaluation reports patients' experience. Design: Multimethod, involving interviews and questionnaires. Setting: 23 general practices in the intervention arm of a cluster randomised controlled trial in East of England and East Midlands, UK. Participants: People on the stroke registers of participating general practices were invited to attend an MLAS programme. Interventions: MLAS comprises one-to-one and group-based sessions to promote independence, confidence and hope. Primary and secondary outcome measures: The primary outcome was uptake of the programme. Participants who declined MLAS were sent a questionnaire to ascertain why. Attendees of four programmes completed evaluation forms. Attendees and non-attendees of MLAS were interviewed. Ad-hoc email conversations with the lead author were reviewed. Thematic analysis was used for qualitative data. Results: 141/420 (34%) participants (mean age 71) attended an MLAS programme and 103 (73%) completed 1. 64/228 (28%) participants who declined MLAS gave reasons as: good recovery, ongoing health issues, logistical issues and inappropriate. Nearly all attendees who completed questionnaires felt that process criteria such as talking about their stroke and outcomes such as developing a strong understanding of stroke had been achieved. Conclusions: MLAS was a positive experience for participants but many stroke survivors did not feel it was appropriate for them. Participation in self-management programmes after stroke might be improved by offering them sooner after the stroke and providing a range of delivery options beyond group-based, face-to-face learning. Trial registration number: NCT03353519, NIH.